Prognostic factors for neonatal mortality at the Agadir regional hospital centre, Morocco: A cohort study - Hanane El Ghazouani, PhD; Laila Lahlou, Pr; Souad Yakini, PhD; Maryama Bou-iselmane, PhD; Jaouad Elkhalladi, PhD; El Arbi Bouaiti, Pr; Amina Barkat, Pr (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: على الرغم من انخفاض معدل وفيات الأطفال حديثي الولادة على مستوى العالم، إلا أن التقدم بطيء للغاية والتأخير ملحوظ بشكل عام في أفريقيا. الهدف من الدراسة هو تحديد العوامل التنبؤية المرتبطة ببقاء الأطفال حديثي الولادة في مركز أكادير الإقليمي للمستشفى، المغرب. طريقة البحث: أجريت دراسة مجموعة استعادية في قسم حديثي الولادة في مركز أكادير الإقليمي للمستشفى. تم تضمين الأطفال حديثي الولادة الذين تتراوح أعمارهم بين صفر و ۲۸ يوما، والذين تم إدخالهم إلى المستشفى بين ۱ يناير و۹ مايو ۲۰۲۲م في هذه الدراسة. تم تحديد عوامل تنبؤية مختلفة في التحليل أحادي المتغير بعد طريقة تحليل بقاء كابلان ماير ومقارنة معدلات البقاء باستخدام اختبار الرتبة اللوغاريتمية. تم استخدام نموذج كوكس لتحديد العوامل المرتبطة ببقاء الأطفال حديثي الولادة. النتائج: تم تضمين ما مجموعه ٦٣٩ مولودا جديدا، تم إدخال ٩٥٬٩٪ منهم إلى المستشفى خلال الأسبوع الأول من حياتهم. توفي ۱۱٥ مولودا، وهو ما يمثل معدل وفيات حديثي الولادة في المستشفى بنسبة ۱۸٪. ومن بين المواليد الذين ماتوا، كانت نسبة ٩۸٬٣٪ وفيات مبكرة لحديثي الولادة. وكانت العوامل المرتبطة بزيادة خطر الوفاة هي الاختناق أثناء الولادة والولادة المبكرة وعمر حديثي الولادة أقل من أو يساوي ٧ أيام وانخفاض الوزن عند الولادة وانخفاض حرارة الجسم. الاستنتاجات: لا يزال معدل وفيات الأطفال حديثي الولادة مرتفعا. إن تطوير مهارات الجهات الفاعلة وتعزيز الفحص للحمل الخطير مع الإنعاش المعزز والرعاية المبكرة للمواليد الجدد أمر ضروري للحد من وفيات الأطفال حديثي الولادة. Abstract: Introduction: Although neonatal mortality is declining globally, progress is slow, particularly in Africa. The goal of this study was to determine the predictive factors associated with survival in newborns at the Agadir Regional Hospital Centre, Morocco. Methods: This retrospective cohort study performed at the neonatology department of the Agadir Regional Hospital Centre included neonates, from birth to 28 days old, who were hospitalized between January 1 and May 9, 2022. Prognostic factors were determined through univariate analysis with the Kaplan–Meier survival analysis method, and survival rates were compared with the log-rank test. The Cox model was used to determine factors associated with neonatal survival. Results: Of 639 enrolled newborns, 95.9 % were hospitalized during the first week of life. A total of 115 newborns died, resulting in an in-hospital neonatal mortality rate of 18 % (95 % CI [15.2–21.2]), and 98.3 % were early neonatal deaths. The factors associated with elevated death risk were perinatal asphyxia (aHR = 2.61, 95 % CI [1.57–4.43], p < 0.001); prematurity (aHR = 2.15, 95 % CI [1.17–3.94], p = 0.013); neonatal age ≤7 days (aHR = 4.89, 95 % CI [1.14–20.94], p = 0.032); low birth weight (aHR = 2.25, 95 % CI [1.28–3.94], p = 0.005); and hypothermia (aHR = 7.60, 95 % CI [1.71–33.73], p = 0.008). Conclusion: The neonatal mortality rate remains high. Developing the skills of healthcare providers, strengthening risk screening for pregnancies, and enhancing resuscitation and early care for newborns are essential to decrease neonatal mortality.